Analisis Kemandirian Siswa Sesuai Profil Pelajar Pancasila melalui Pendekatan Project Based Learning di Sekolah Dasar - Riska Novalia (Bima Journal of Elementary Education, 2023)
This study is explore and analyze the level of elementary school students' independence in accordance with the Pancasila student profile through the Project Based Learning approach. The research objective is to understand the extent to which the implementation of Project Based Learning can enhance students' independence in understanding the values of Pancasila. The research method involves the population of elementary school students and purposive sampling. Data analysis techniques include qualitative and quantitative analysis. The research results indicate an improvement in students' independence in understanding and applying the values of Pancasila through the implementation of Project Based Learning. The conclusion of this study is that Project Based Learning is an effective approach to enhance students' independence in understanding and embodying the values of Pancasila in elementary school. Recommendations for future research include deepening the study by involving more variables and expanding the research scope to various elementary schools.